Minimally Invasive Redo Mitral Valve Replacement: The Good, Bad and Ugly - Sazzad, Md Faizus (National Heart Foundation Hospital & Research Institute, 2021)
Conference on Cardiovascular Disease, National Heart Foundation of Bangladesh